Binge-Like Sucrose Self-Administration Experience Inhibits Cocaine and Sucrose Seeking Behavior in Offspring - Le, Qiumin; Li, Yanqing; Hou, Weiqing; Yan, Biao; Yu, Xiangchen; Song, Haikun; Wang, Feifei; Ma, Lan (Frontiers in Behavioral Neuroscience, 2017)
Recent studies show that emotional and environmental stimuli promote epigenetic inheritance and influence behavioral development in the subsequent generations. Caloric mal- and under-nutrition has been shown to cause metabolic disturbances in the subsequent generation, but the incentive properties of paternal binge-like eating in offspring is still unknown. Here we show that paternal sucrose self-administration experience could induce inter-generational decrease in both sucrose and cocaine-seeking behavior, and sucrose responding in F1 rats, but not F2, correlated with the performance of F0 rats in sucrose self-administration. Higher anxiety level and decreased cocaine sensitivity were observed in Sucrose F1 compared with Control F1, possibly contributing to the desensitization phenotype in cocaine and sucrose self-administration. Our study revealed that paternal binge-like sucrose consumption causes decrease in reward seeking and induces anxiety-like behavior in the F1 offspring.